Ecotoxicological and health risk assessing of heavy metals and microplastics in African catfish (Clarias gariepinus) of Burullus Lake, Egypt - Muhammad A. El-Alfy; Marwa M. AbouHadied; Tahany A. Ismail (Environmental Science and Pollution Research, 2026)

Exploiting the biocontrol potential of Chaetomium globosum against Fusarium solani root rot in wheat: climate-responsive phytohormonal regulation, genetic diversity, and sustainable management - Marwa S. Fouad; Khaled M. A. Ramadan; Hisham A. Mohamed; Mohamed Abou-Zeid; Shafik D. Ibrahim; Muhammad Munir; Eslam S. A. Bendary; Mohamed M. Aboul Fotouh; Sallah A. Al Hashedi; Adil AlShoaibi; Zafar Iqbal; Ahmed M. Ismail; et al. (European Journal of Plant Pathology, 2026)

Provenance, tectonic settings, depositional conditions, and diagenetic features of the late Cretaceous (Coniacian–Santonian) Fika Shale, Upper Benue Trough, Northeastern Nigeria: Implications for hydrocarbon potential - Abdulwahab Bello; Musa B. Usman; Shehu Mukkafa; Ibrahim A. Kwami; Usman Abubakar; Abduljamiu O. Amao; Anas M. Salisu; Khalid Al-Ramadan; Muhammad A. Ismail; Abubakar S. Maigari; Ahmed I. Haruna; Bandar D. Al-Otaibi; et al. (Journal of African Earth Sciences, 2026)

The emerging and escalating consequences of rural depopulation in the Himalaya - Karuna Budhathoki; Bhola Bhattarai; Bed Mani Dahal; Shalini Dhyani; Ambika P. Gautam; Binita Guragain; Dibya Devi Gurung; Muhammad Ismail; Om Katel; Sarala Khaling; Kristina Marquardt; Ulrike Müller-Böker; et al. (Global Environmental Change, 2026)

Where waters transform: Hydrographic variability and turbulent mixing in the lifamatola passage, Indonesia - Adi Purwandana; Zheng Wang; Rui Li; Zhenhua Xu; Yao Li; Dewi Surinati; Fuad Azminuddin; Bayu Priyono; Dwiyoga Nugroho; Muhammad R. Cordova; Teguh Agustiadi; Mochamad R. Iskandar; et al. (Progress in Oceanography, 2026)

Modulating the thermo-immuno-endocrine axis to alleviate heat stress in poultry: A pharmacological perspective - Mohamed E. Abd El-Hack; Ahmed I. Elsherbeni; Amira K. Hajri; Marzough A. Albalawi; Mohamed AbdElrahman; Mahmoud Moustafa; Mohammed Al-Shehri; Muhammad Asif Arain; Ismail E. Ismail (Journal of Thermal Biology, 2026)

Unveiling Morpho-Anatomical Strategies of Cenchrus Ciliaris L. for Survival under Vehicular Pollution Stress - Hafiz Muhammad Mohsin Hassan; Muhammad Akram; Imran Haider; Muhammad Altaf Nazir; Lamy Hamed; Abdullateef Al-Saeed; ElSayed A. Badr; Ahmed Ismail (Water, Air, & Soil Pollution, 2026)

Myricetin as a potential therapeutic agent against Pseudomonas aeruginosa : inhibition of biofilm formation, quorum sensing, and virulence factor production - Sallah A. Al Hashedi; Saif M. Dmour; Hamad Sarheed Galut; Ayman Daifallah Ismail Alsheikh; Mohammad H. Abukhalil; Sham Ma’aitah; Najeeb S. Al-Zoreky; Khaled M.A. Ramadan; Muhammad Naeem Sattar; Zafar Iqbal; Adil Alshoaibi; Sultan A. M. Saghir (Biofouling, 2026)

Hydrothermal synthesis of novel Mn3O4-Nd2O4 nano-hybrid as bi-functional electrocatalyst for water splitting - Muhammad Ibrar; Iram Manzoor; Mostafa A. Ismail; Misbah Shareef; Habiba Batool; Sana Ben Khalifa; Saleh Chebaane; Zeineb Klai (Fuel, 2026)

Technological trends in rainwater harvesting for micro-hydropower: a scientometric review - S. N. F. Abdullah; M. K. A. Kamarudin; N. A. Wahab; N. Yaakub; A. S. Mohd Saudi; M. N. A. Rahman; S. Sunardi; F. Muhammad-Sukki; I. N. Ismail (International Journal of Energy and Water Resources, 2026)

Development of rare earth metal-supported manganese selenide (MnSe2-Nd2O3) heterostructure enabling robust hydrogen evolution reaction - Muhammad Abdul; Chingmai Ko; Mostafa A. Ismail; Sana Ben Khalifa; Norah A.M. Alsaif; Saleh Chebaane; Jehan Akbar; Suleyman I. Allakhverdiev (Fuel, 2026)

Metal-organic framework-derived defect-enriched bimetallic Cerium/Manganese oxide nanocomposite with carbon for boosted water electrolysis and supercapacitor applications - Tauseef Munawar; Ambreen Bashir; Sonia Sardar; Muhammad Rafaqat; Guo Changqing; Mostafa A. Ismail; Shoukat Alim Khan; Muammer Koc; Suleyman I. Allakhverdiev; Faisal Iqbal; Chang-Feng Yan (Fuel, 2026)

Modelling of electrolyzers and fuel cells for grid services under high RES penetration - Sulaiman S. Ahmad; Abdullah A. Almehizia; Muhammad Khalid; Fahad Saleh Al-Ismail (Next Research, 2025)

Recent advancements in UiO-66(Zr) MOFs and their derivatives: Designing water-stable membranes for water applications - Yahaya A. Muhammad; Muhammad Sajid; Abubakar Umar; Niaz Ali Khan; Ismail Abdulazeez; Billel Salhi; Nadeem Baig; Wail Falath (Desalination, 2025)

Comprehensive investigation of the smouldering characteristics of hemic peat under varying moisture conditions and the combined influence of wind velocity and direction - Nor Azizah Che Azmi; Ahmad Safuan A Rashid; Nazirah Mohd Apandi; Abd Wahid Rasib; Mohd Nazri Mohd Nasir; Adnan Zainorabidin; Mohamad Sofi Mohamed; Muhammad Amir Mat Shah; Diana Che Lat; Afiqah Ismail (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Recent advances in layered double hydroixdes@MXene (LDHs@MXene) composites: Synthesis, properties, and catalytic applications - Sundas Riaz; Sami Ullah; Sanam Bashir; Aziz ur Rehman; Rashid Iqbal; Tayyaba Najam; Mostafa A. Ismail; Md Rezaul Karim; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Applied Clay Science, 2025)

Fabrication and characterization of bioactive curdlan and sodium alginate films for enhancing the shelf life of Volvariella volvacea - Asif Ali Khan; Feng-Jie Cui; Muhammad Wajid Ullah; Abdul Qayum; Ibrahim Khalifa; Syed Asim Shah Bacha; Zheng-Zi Ying; Ismail Khan; Umar Zeb; Abdullah A. Alarfaj; Mohammad Javed Ansari; Yan Yang; et al. (Food Bioscience, 2024)

Deciphering the differential expression patterns of yield-related negative regulators in hexaploid wheat cultivars and hybrids at different growth stages - Muhammad Jawad Akbar Awan; Muhammad Awais Farooq; Rubab Zahra Naqvi; Umer Karamat; Sayyad Ali Raza Bukhari; Muhammad Abu Bakar Waqas; Muhammad Arslan Mahmood; Muhammad Ismail Buzdar; Awais Rasheed; Imran Amin; Nasir A. Saeed; Shahid Mansoor (Molecular Biology Reports, 2024)

Machine learning modeling and statistical optimization of dye removal from contaminated water using CTAB-functionalized graphene oxide - Sally AlNaimat; Usman M. Ismail; Ahmed I. Ibrahim; Abdimalik Muse; Kashif Faheem; Mohamed Mustafa; Muhammad S. Vohra; Sagheer A. Onaizi (Water, Air, & Soil Pollution, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Aflatoxins in the rice production chain: A review on prevalence, detection, and decontamination strategies - Iqra Naeem; Amir Ismail; Muhammad Riaz; Mubashir Aziz; Kashif Akram; Muhammad A. Shahzad; Mavra Ameen; Sher Ali; Carlos A.F. Oliveira (Food Research International, 2024)

Maximizing energy via solar‐powered smart irrigation: An approach utilizing a single‐axis solar tracking mechanism - Firas Basim Ismail; Muhammad Aqil Afham Rahmat; Hussein A. Kazem; Abdulkareem Sh. Mahdi Al‐Obaidi; Muhammad Syauqi Ridwan (Irrigation and Drainage, 2024)
This study presents and assesses the novelty of a cutting‐edge solar‐powered automated irrigation system that incorporates a single‐axis solar tracker. The research entails the meticulous development of a prototype, followed by comprehensive experimental scrutiny spanning 3 days, from 8:00 AM to 6:00 PM. In a unique approach, we benchmark the findings against previous research endeavours, highlighting the transformative potential of our innovative design. Our innovative system harnesses a singular‐axis solar tracking mechanism alongside moisture sensors and a water pump relay module, resulting in the creation of an autonomous irrigation system perpetually powered by solar energy. The results are noteworthy, showcasing the capability of a solar panel equipped with single‐axis tracking to significantly boost photovoltaic output power. This configuration attains a remarkable 65% increase in total output power and a substantial improvement over the modest 52%–53% performance of fixed solar panels. This substantial divergence translates to a noteworthy 12%–13% difference in efficacy, underscoring the pioneering nature of our research. The zenith of power output, ranging between 3.16 and 3.68 W, transpires from noon to 2:00 PM, further illustrating the system's viability. The integrated water pump exhibits commendable efficiency, attaining levels as high as 75%. This revelation underscores the transformative potential of automated irrigation systems endowed with single‐axis solar tracking technology, auguring amplified system performance and heralding a new era of sustainable agricultural practices.

Adsorptive removal of heavy metals from aqueous solutions: Progress of adsorbents development and their effectiveness - Usman M. Ismail; Muhammad S. Vohra; Sagheer A. Onaizi (Environmental Research, 2024)

Synergistic effect of Bacillus subtilis and benzothiadiazole (Bion®) on the suppression of Fusarium oxysporum and the enhancement of disease resistance in Capsicum annuum - Kamal A. M. Abo-Elyousr; Nashwa M.A Sallam; Magdy A. A Mousa; Muhammad Imran; Ismail R. Abdel-Rahim (Journal of Plant Pathology, 2023)

Linking diagenesis and reservoir quality to depositional facies in marginal to shallow marine sequence: An example from the Campano-Maastrichtian Gombe Sandstone, Northern Benue Trough, NE Nigeria - Abdulwahab M. Bello; Musa B. Usman; Muhammad A. Ismail; Shehu Mukkafa; Usman Abubakar; Ibrahim A. Kwami; Khalid Al-Ramadan; Abduljamiu O. Amao; Murtada Al-Hashem; Anas M. Salisu; Aliyuda Kachalla; Muhammad B. Abubakar; et al. (Marine and Petroleum Geology, 2023)

A review on revolutionary technique for phosphate removal in wastewater using green coagulant - Amina A. Owodunni; Suzylawati Ismail; Setyo Budi Kurniawan; Azmi Ahmad; Muhammad Fauzul Imron; Siti Rozaimah Sheikh Abdullah (Journal of Water Process Engineering, 2023)

Rapeseed increases cadmium concentration of wheat in a rotation system through suppressing root mycorrhizal activity of wheat - Muhammad Asif; Idil Ertem; Huseyin Beyaz; Cynthia A. Grant; Hans Lambers; Ismail Cakmak (Plant and Soil, 2023)

Functionalized graphene oxide-zinc oxide hybrid material and its deployment for adsorptive removal of levofloxacin from aqueous media - Nimra Ismail; Muhammad Imran; Muhammad Ramzan; Ayesha Anwar; Ibrahim A. Alsafari; Muhammad Asgher; Hafiz M.N. Iqbal (Environmental Research, 2023)

Effect of Different Solubilization pH Values on the Functional Properties of Protein Spirulina platensis Isolated Through Acidic Precipitation - N. A. Kamaruding; N. A. Muhammad Daud; N. Ismail; S. Shaharuddin (Journal of Aquatic Food Product Technology, 2022)

Cowpea induced physicochemical and biological rhizosphere changes in hydrocarbon contaminated soil - A. A. Farouq; H. Y. Ismail; A. B. Rabah; A. B. Muhammad; U. B. Ibrahim; A. Y. Fardami (Plant and Soil, 2022)

Controlling of Xanthomonas axonopodis pv. phaseoli by induction of phenolic compounds in bean plants using salicylic and benzoic acids - Kamal A. M. Abo-Elyousr; Muhammad Imran; Najeeb M. Almasoudi; Esmat F. Ali; Sabry Hassan; Nashwa M A. Sallam; Khamis Youssef; Ismail R. Abdel-Rahim; Hadeel M.M. Khalil Bagy (Journal of Plant Pathology, 2022)

Hypercholesterolemia and 27-Hydroxycholesterol Increase S100A8 and RAGE Expression in the Brain: a Link Between Cholesterol, Alarmins, and Neurodegeneration - Raúl Loera-Valencia; Muhammad-Al-Mustafa Ismail; Julen Goikolea; Maria Lodeiro; Laura Mateos; Ingemar Björkhem; Elena Puerta; Mariana A. Romão; Cláudio M. Gomes; Paula Merino-Serrais; Silvia Maioli; Angel Cedazo-Minguez (Molecular Neurobiology, 2021)
Alterations in cholesterol metabolism in the brain have a major role in the physiology of Alzheimer’s disease (AD). Oxysterols are cholesterol metabolites with multiple implications in memory functions and in neurodegeneration. Previous studies have shown detrimental effects of cholesterol metabolites in neurons, but its effect in glial cells is unknown. We used a high-fat/high-cholesterol diet in mice to study the effects of hypercholesterolemia over the alarmin S100A8 cascade in the hippocampus. Using CYP27Tg, a transgenic mouse model, we show that the hypercholesterolemia influence on the brain is mediated by the excess of 27-hydroxycholesterol (27-OH), a cholesterol metabolite. We also employed an acute model of 27-OH intraventricular injection in the brain to study RAGE and S100A8 response. We used primary cultures of neurons and astrocytes to study the effect of high levels of 27-OH over the S100A8 alarmin cascade. We report that a high-fat/high-cholesterol diet leads to an increase in S100A8 production in the brain. In CYP27Tg, we report an increase of S100A8 and its receptor RAGE in the hippocampus under elevated 27-OH in the brain. Using siRNA, we found that 27-OH upregulation of RAGE in astrocytes and neurons is mediated by the nuclear receptor RXRγ. Silencing RXRγ in neurons prevented 27-OH-mediated upregulation of RAGE. These results show that S100A8 alarmin and RAGE respond to high levels of 27-OH in the brain in both neurons and astrocytes through RXRγ. Our study supports the notion that 27-OH mediates detrimental effects of hypercholesterolemia to the brain via alarmin signaling.

Acetylcholinesterase and α-glucosidase inhibitory compounds from Callicarpa maingayi - Muhammad A. Ado; M. Maulidiani; Intan Safinar Ismail; Hasanah M. Ghazali; Khozirah Shaari; Faridah Abas (Natural Product Research, 2021)

Arsenic and lead in the indoor residential settings of different socio-economic status; assessment of human health risk via dust exposure - Nadeem Ali; Syed Ali Musstjab Akber Shah Eqani; Ehtisham Nazar; Nabil A. Alhakamy; Muhammad Imtiaz Rashid; Khurram Shahzad; Jahan Zeb; Heqing Shen; Iqbal Mohammad Ibrahim Ismail; Hussain Mohammed Salem Ali Albar (Environmental Science and Pollution Research, 2021)

Skill and predictability in multimodel ensemble forecasts for Northern Hemisphere regions with dominant winter precipitation - Muhammad Azhar Ehsan; Michael K. Tippett; Mansour Almazroui; Muhammad Ismail; Ahmed Yousef; Fred Kucharski; Mohamed Omar; Mahmoud Hussein; Abdulrahman A. Alkhalaf (Climate Dynamics, 2017)

Permian ultrafelsic A-type granite from Besar Islands group, Johor, peninsular Malaysia - Azman A Ghani; Fatin Izzani Hazad; Azmiah Jamil; Quek Long Xiang; Wan Nur Atiqah Wan Ismail; Sun-Lin Chung; Yu-Ming Lai; Muhammad Hatta Roselee; Nur Islami; Kyaw Kyaw Nyein; Meor Hakif Amir Hassan; Mohd Farid Abu Bakar; et al. (Journal of Earth System Science, 2014)

Development of a Polygonum minus cell suspension culture system and analysis of secondary metabolites enhanced by elicitation - Muhammad Faizan A. Shukor; Ismanizan Ismail; Zamri Zainal; Normah Mohd Noor (Acta Physiologiae Plantarum, 2013)